2012
DOI: 10.2139/ssrn.2192520
|View full text |Cite
|
Sign up to set email alerts
|

Kaldor-Verdoorn's Law and Increasing Returns to Scale: A Comparison Across Developed Countries

Abstract: We are thankful to Mario Centorrino, Matteo Lanzafame and to the session participants at the AISSEC conference (Perugia, 2009) for helpful comments and suggestions. The usual disclaimer applies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
13
2
Order By: Relevance
“…The results also show that growth in industrial output will lead to increased labor productivity, in this sector, but with an elasticity coefficient equal to 0.81 for the whole and 0.616 for the industry sector. These results contradict the findings of several studies, specifically Romero and McCombie (2016) and Millemaci and Ofria (2014), whose studies supported the hypothesis of increasing returns to scale in manufacturing sector in developed countries.…”
Section: Results and Recommendationscontrasting
confidence: 99%
See 2 more Smart Citations
“…The results also show that growth in industrial output will lead to increased labor productivity, in this sector, but with an elasticity coefficient equal to 0.81 for the whole and 0.616 for the industry sector. These results contradict the findings of several studies, specifically Romero and McCombie (2016) and Millemaci and Ofria (2014), whose studies supported the hypothesis of increasing returns to scale in manufacturing sector in developed countries.…”
Section: Results and Recommendationscontrasting
confidence: 99%
“…Millemaci and Ofria (2014) examined whether the degree of increasing returns to scale varies through time, estimating Kaldor–Verdoorn’s law for different periods through 1973–2006 for ten EU countries. They suggested that the Verdoorn coefficient has been stable during the period for the countries individually considered.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiménez-Rodríguez 2008;Sánchez 2005, 2009) and it is commonly used in the works on the Smith-Kaldor-Verdoorn law (e.g. Millemaci and Ofria 2014). While oil price affects the value added, labour productivity is unlikely to affect the oil price directly.…”
Section: Data and Methodological Issues With The Benchmark Modelmentioning
confidence: 99%
“…In the shadows of exogenous growth theory, there have remained economists who have studied the ways that activist policy can have long-term effects by raising productivity (Dixon and Thirlwall 1975; Millemaci and Ofria 2012; Verdoorn 2002). Writing (in Italian) shortly after the Great Depression and World War II, the Dutch economist Petrus Verdoorn estimated that productivity growth accounts for nearly half of increased output during booms.…”
Section: Direct Effects Of Demand On Productivitymentioning
confidence: 99%